The mediating role of academic and emotional self-efficacy in the relationship between mindful attention awareness and academic self-regulation - Abdel Hadi, Samer; Al-Quraan, Mahmoud (Frontiers in Education, 2025)
IntroductionUnderstanding the role of academic and emotional self-efficacy in the relationship between mindful attention awareness and academic self-regulation among university students can help enhance students’ academic performance and well-being by illuminating the psychological processes linking mindful attention awareness to academic self-regulation. Studies link mindfulness with self-regulation; however, whether academic and emotional self-efficacy mediates this correlation among students has yet to be studied.MethodsWe test a structural model to clarify these relations and their implications for academic performance. This study examined the relationship between mindful attention awareness and academic self-regulation, exploring the mediating roles of academic and emotional self-efficacy. Survey research has been used in the current study. The Mindful Attention Awareness Scale (MAAS), the Academic Self-Efficacy Scale (ASES), the Emotional Self-Efficacy Scale (ESES), and the Academic Self-Regulation Scale (ASRS) were administered with undergraduate students (n = 647), most were female (77.1%), aged between 18 and 24 (74.5%), and enrolled primarily in undergraduate programs (91.8%). Most participants were studying humanities and social sciences (56.9%) and resided in the Asian region (87.8%).ResultsThe results showed that academic self-efficacy positively affects self-planning, self-monitoring, self-instruction, and self-reaction. No significant relationship emerged between the self-evaluation subscale of academic self-regulation and academic self-efficacy. Mindful attention awareness did not show statistically significant correlation with emotional self-efficacy.DiscussionOur study results demonstrate that academic self-efficacy is a key construct linking mindfulness practices and academic self-regulation, but emotional self-efficacy did not mediate the relationship between mindfulness and academic self-regulation, highlighting the need for more rigorous research into its role in academic contexts.